Potential reduction of CO2 emissions which is the cause of greenhouse gasses during COVID-19 - Ismail, Yunita; Khusniyati, Arika (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Greenhouse Gas Carbon Emissions produced in the implementation of education in tertiary institutions can be said to be quite high. Activities during the COVID-19 pandemic carried out by countries in the world have had many unexpected positive impacts by reducing CO2 emissions by up to 70%. At the beginning of 2020, various countries in the world including Indonesia and Jakarta experienced the COVID-19 pandemic, which prompted the government to implement the Large-Scale Social Restrictions (PSBB) policy to suppress cases of the spread of COVID-19. The existence of the PSBB has an impact on various aspects of people's lives, including limitations on community activities and mobility using motorized vehicles. The purpose of this study was to determine the amount of CO2 emissions during the PSBB policy period. Methods: The method and results given are a calculation method taken from several journals, and websites that are methods and models of emission reduction using expert opinion methods. One of them is the method used by the Intergovernmental Panel on Climate Change (IPCC), which is the most up-to-date method today. Findings: The decrease in CO2 emissions during lockdown is caused by changes in people's activities outside the home, fuel consumption, and people's mobility using motorized vehicles. The COVID-19 pandemic, especially the implementation of lockdown, can be used as a momentum in increasing efforts and strategies to reduce the amount of CO2 emissions from motorized vehicles, one of which is by implementing low-carbon development. Conclusion: As we know in 2019, there is a COVID-19 pandemic which is one of the factors for reducing carbon dioxide emissions. Novelty/Originality of this Study: This study provides a novel contribution by quantitatively assessing CO2 emission reductions during the COVID-19 lockdown, emphasizing the unique context of an unprecedented global event. It conducts a comprehensive literature review to integrate various CO2 calculation methods, particularly highlighting the sophisticated IPCC method, and offers a comparative analysis of emission reduction techniques.